A Study on Perception Gaps in Autonomous Vehicle Technologies and Their Implications for AV Transport System Deployment: An Integrated AHP–T-Test Approach - Yoon, SeongJeong; Kim, MinYong (Environment and Social Psychology, 2025)
This study aims to analyze the perception gap between users’ expectations and the actual performance of autonomous vehicle (AV) technologies, and to examine how these gaps influence the deployment of AV-based transport services such as autonomous taxis, shuttles, and mobility-as-a-service (MaaS). A total of 107 users with experience in Level 2–3 autonomous driving systems participated in a structured survey evaluating expectations and satisfaction across three domains: Technology (decision-making, control, communication), Safety (driver monitoring, takeover request, emergency handling, system redundancy), and Convenience (long-distance support, lane automation, vehicle condition monitoring). Paired-samples t-tests revealed a significant gap in decision-making technology and statistically significant expectation–performance discrepancies in all Safety and Convenience items. System redundancy recorded the largest gap, indicating users’ strong concerns about fail-safe capability. To identify priority areas for AV service deployment, an Analytic Hierarchy Process (AHP) framework was constructed. The results showed that users prioritize Safety Assurance (0.38), whereas manufacturers and engineering experts assign the highest importance to Decision-Making Technology (0.34). These differing priorities highlight a structural misalignment between supply-side development strategies and demand-side expectations, which may influence public acceptance, operational reliability, and regulatory planning for AV transport systems. This study contributes to the literature by integrating perception-gap analysis with a technology prioritization model, offering actionable insights for future AV system design, service planning, and safety policy formulation.